2013
DOI: 10.1111/j.1600-6143.2012.04340.x
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Application for Initial Screening of Living Kidney Donors: Development, Implementation and Evaluation

Abstract: Most centers utilize phone or written surveys to screen candidates who self-refer to be living kidney donors. To increase efficiency and reduce resource utilization, we developed a web-based application to screen kidney donor candidates. The aim of this study was to evaluate the use of this web-based application. Method and time of referral were tabulated and descriptive statistics summarized demographic characteristics. Time series analyses evaluated use over time. Between January 1, 2011 and March 31, 2012, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…These same living donation informational packets are distributed to local dialysis units. Potential living donors can contact the transplant center via phone or through a web-based application (16). …”
Section: Introductionmentioning
confidence: 99%
“…These same living donation informational packets are distributed to local dialysis units. Potential living donors can contact the transplant center via phone or through a web-based application (16). …”
Section: Introductionmentioning
confidence: 99%
“…Quasiexperimental studies were studies that were experimental in nature but lacking random assignment. Six articles (Table 3) were quasiexperimental studies, including controlled before and after or interrupted time series (22)(23)(24)(25)(26)(27). Unlike RCTs, the strategies to increase donation varied and included education (n=1), campaign (n=1), removal of disincentives (donor reimbursement, leave policies, and tax benefits; n=3), and an intervention that examined the effect of a web-based survey to enable screening of potential donors by providing an immediate response regarding the potential donor's candidacy.…”
Section: Quasiexperimental Studiesmentioning
confidence: 99%
“…Among the other interventions identified in quasiexperimental studies, three examined removal of disincentives (24)(25)(26); although all three found a positive trend toward increasing living donors, none of the studies reported statistically significant differences. One study reported on a novel web-based intervention for potential donors to selfscreen themselves as candidates (27). They found that a web-based tool significantly increased the number of contacts with the transplant center; the study also found an increase in the number of living donors and living donor evaluations but did not report whether these findings were significant.…”
Section: Quasiexperimental Studiesmentioning
confidence: 99%
“…Only 43% of centers met reporting thresholds for LKDs who donated in 2013, indicating that novel methods for collecting LKD follow-up data are needed. [10][11][12][13][14][15][16][17][18][19][20] However, mHealth technology has not yet been explored as a method for improving LKD follow-up, despite the well-documented challenges of collecting follow-up data. 9 Within the transplant community, mHealth technologies have been used to address numerous challenges in the field, including educating transplant recipients and candidates, improving adherence and self-management behaviors of recipients, helping patients on the waitlist find a living donor, and aiding in the screening and evaluation process of LKD candidates.…”
Section: Introductionmentioning
confidence: 99%
“…9 Within the transplant community, mHealth technologies have been used to address numerous challenges in the field, including educating transplant recipients and candidates, improving adherence and self-management behaviors of recipients, helping patients on the waitlist find a living donor, and aiding in the screening and evaluation process of LKD candidates. [10][11][12][13][14][15][16][17][18][19][20] However, mHealth technology has not yet been explored as a method for improving LKD follow-up, despite the well-documented challenges of collecting follow-up data. Improved follow-up data collection is needed to improve understanding of long-term risks associated with live donor nephrectomy, as existing analyses are limited by incomplete LKD follow-up data.…”
Section: Introductionmentioning
confidence: 99%